Penerapan Model Pembelajaran Scramble terhadap Hasil Belajar IPAS Siswa Kelas V SD Negeri 85 Lubuklinggau - Syara Aprilia; Ahmad Gawdy Prananosa; Yetty Trisnayanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Student learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level remain suboptimal because the instructional process is dominated by lecture methods, resulting in low student engagement. One alternative to address this issue is the implementation of the "Scramble" learning model, which encourages active student participation through activities involving the matching of questions and answers. This study aims to determine the learning mastery of fifth-grade students at SD Negeri 85 Lubuklinggau in IPAS following the implementation of the Scramble learning model. The study employs an experimental method using a One-Group Pretest-Posttest design. The population consists of all 25 fifth-grade students at SD Negeri 85 Lubuklinggau during the 2025/2026 academic year. A non-probability sampling technique was used, resulting in a sample comprising the entire group of 25 fifth-grade students. Data collection was conducted using multiple-choice learning outcome tests administered before and after the intervention. Data analysis involved normality and hypothesis testing at a significance level of α = 0.05. The results indicate that the average pre-test score was 57.2, with a learning mastery rate of 16% (4 students meeting the mastery criterion/KKTP). Following the implementation of the Scramble learning model, the average post-test score rose to 87.6, with a learning mastery rate of 92% (23 students meeting the KKTP). Hypothesis testing results show that t-calculated (4.24) > t-table (2.06); thus, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Consequently, it can be concluded that the implementation of the Scramble learning model has a significant effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 85 Lubuklinggau and enables the achievement of learning mastery.